Social Media Addiction in Geopolitically At-Risk Youth. - Mahamid, Fayez Azez; Berte, Denise Ziya (International Journal of Mental Health & Addiction, 2019)
The concept of an addictive process related to social media use, specifically for youth, has been explored in several venues including the attempt to identify factors of vulnerability in predicting excessive or maladaptive use of social media. While the focus has been on personal characteristics, there are also clear environmental stressors or situational variables that affect particular populations that might contribute to patterns of addictive social media use, such as limited social and recreational outlets, restricted movement, and access to in-person socialization with peers, as well as stress related to local geographic political conflict. The current study examines the concept of geopolitical vulnerability related to living in a militarized occupied area and patters of maladaptive addicted social media use in young adults. The sample included 744 students at An-Najah National University of Palestine all residing in the occupied West Bank of Palestine. The results indicate that the level of maladaptive use of social media is high with a vast majority of students scoring within the range of an addictive pattern of use (47%). These findings are qualified by the variables of gender, with males at highest risk, and level of study with bachelor level students exhibiting significantly more addictive behaviors than master's level students in regard to social media. In a geopolitical area with high stress and few opportunities for leisure activities or open socialization, it is not difficult to imagine a heightened vulnerability to an addictive pattern of social media use given its continual availability, relative easy access, and contrived feeling of social satisfaction for youth. However, this virtual "fix" may come at a high price for developing adults who lack social skills for their challenging environments, are unable to discern reality from the fantasy of social media, and are creating habits that will be formative in their adulthood. Further investigation is needed to examine the specific risks of excessive social media use and structural societal changes needed to add protective factors to combat social media addiction in the upcoming generations in high stress areas.